The effects of reducing dietary crude protein and/or adding chicory on composition and odor of stored swine manure - Hanni, S.M.; Groesbeck, C.N.; Young, M.G.; Lawrence, K.R.; DeRouchey, Joel M.; Tokach, Michael D.; Nelssen, Jim L.; Goodband, Robert D.; Dritz, Steven S. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2009)
A feeding study was conducted to compare nutrient excretion and odor analysis of pigs fed either a conventional corn-soybean meal diet, or a diet formulated to minimize nutrient excretion and odors through use of crystalline amino acids, phytase, and nonsulfur containing trace minerals. These diets (0.85% true digestible lysine), were fed to pigs (each initially 130 lb) with or without chicory, a feed ingredient speculated to reduce odors in swine waste. Dietary treatments were arranged in a 2 x 2 factorial, with main effects of diet nutrient excretion potential (low or high) and chicory (0 or 10%). Twelve nonlittermate barrows were fed each of the four diets over four, 10-d periods in a replicated 4 × 4 Latin square design. Each pig was housed in a stainless steel metabolism cage (5 × 2 ft) designed to allow separate collection of urine and feces. Feces and urine were collected between the seventh and eleventh meals in order to measure nitrogen (N), sulfur (S), and phosphorus (P) intake, excretion, and retention. Feces and urine also were collected the last two days of each period and mixed into a 7.5% DM slurry for odor analysis at the University of Minnesota Olfactometry Laboratory. The 7.5% DM slurries were measured for pH, total solids (TS), total volatile solids (TVS), ammonia, total Kjeldahl nitrogen (TKN), hydrogen disulfide (H2S), percentage sulfur (sum of sulfur in air and slurry samples), and Ca, K, Mg, Na, and P. Air samples collected from the slurries were measured for H2S, intensity, and offensiveness. Pigs fed diets formulated to reduce nutrient excretion and odor had a 20% and 34% reduction (P<0.001) in total N and P excretion, respectively, and a 33% reduction in urinary S excretion. The addition of chicory to the diet further reduced (P<0.002) N and P excretion by 10% and 14%, respectively. Pigs fed the diets formulated to reduce nutrient excretion and odor had lower (P<0.001) total pH, ammonia, sulfur dry weight percentage, and TKN in the slurry samples. However, H2S emission, odor intensity and offensiveness were not affected (P<0.19). These results indicate that formulating a diet to meet the needs of a pig, yet lower nutrient excretion by use of synthetic amino acids, phytase, nonsulfur-containing trace mineral premixes and the addition of chicory will reduce nutrient excretion in swine manure, but do not appear to affect the intensity or offensiveness of odors.
Keywords: Pigs; Chicory; Odor; Nutrient Excretion; Phytase; Swine